2018
DOI: 10.2174/1871521409666170412121820
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel 1, 3- thiazolidine-2, 4-diones as Anti-prostate Cancer Agents

Abstract: These findings may provide the essential information for the development of anti-prostate cancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Excessive peroxynitrite radical can be produced by endothelial NO synthase, inducible NO synthase, and neural NO synthase and also produced by the reaction with O 2− , and it might cause many pathological degenerative disorders such as cancer, inflammatory, neurodegenerative, and oxidative damage. [ 12 16 21 22 ] Previous studies have demonstrated that polyphenolic compounds would be the major factor for NO prevention, which might be the reason behind differential inhibitory effects observed in our previous study. [ 2 12 16 17 21 ] In the present study, NO was remarkably inhibited by all the fractions of A. viridis extracts in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Excessive peroxynitrite radical can be produced by endothelial NO synthase, inducible NO synthase, and neural NO synthase and also produced by the reaction with O 2− , and it might cause many pathological degenerative disorders such as cancer, inflammatory, neurodegenerative, and oxidative damage. [ 12 16 21 22 ] Previous studies have demonstrated that polyphenolic compounds would be the major factor for NO prevention, which might be the reason behind differential inhibitory effects observed in our previous study. [ 2 12 16 17 21 ] In the present study, NO was remarkably inhibited by all the fractions of A. viridis extracts in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 86%
“…[ 12 16 21 22 ] Previous studies have demonstrated that polyphenolic compounds would be the major factor for NO prevention, which might be the reason behind differential inhibitory effects observed in our previous study. [ 2 12 16 17 21 ] In the present study, NO was remarkably inhibited by all the fractions of A. viridis extracts in a dose-dependent manner. In addition, we further confirm that different fractions of A. viridis showed an excellent metal chelating ability with low IC 50 value.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations